Female leadership in the Ecuadorian online newspapers El Comercio and El Universo - Baquerizo Neira, Gabriela (2019)
Last couple of years, female presence has increased in Ecuadorian political institutions. However, the visibility of women in the public media continues to be limited. In this context, we investigate how these women are represented by the digital media. We conducted a descriptive study of the socio-demographic characterization of women in published opinion in the digital newspapers El Universo and El Comercio. We identify to what extent these media take women as a reference in their publications, and what are the female profiles in this regard. Through a number of 2,203 press-releases published between 2010 and 2015, we analyze the frequency of appearance of 78 women referred as sources of news. In general, we observe that women consulted as journalistic sources in digital newspapers fluctuate between 35 and 50 years of age, more than 50% identify themselves as mestizas, and most of them have university studies.